2017
DOI: 10.1016/j.eurpsy.2017.01.1904
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Face Recognition in Bipolar Disorder

Abstract: IntroductionEmotional face recognition is significant for social communication. This is impaired in mood disorders, such as bipolar disorder. Individuals with bipolar disorder lack the ability to perceive facial expressions.ObjectivesTo analyse the capacity of emotional face recognition in subjects diagnosed with bipolar disorder.AimsTo establish a correlation between emotion recognition ability and the evolution of bipolar disease.MethodsA sample of 24 subjects were analysed in this trial, diagnosed with bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Abnormalities in emotion recognition (Castellano et al, 2015;Daros, Zakzanis, & Rector, 2014;Elferink, van, & Kessels, 2015;Homorogan et al, 2017;Kohler, Walker, Martin, Healey, & Moberg, 2010) and verbal fluency (Cardenas, Kassem, Brotman, Leibenluft, & McMahon, 2016;Clark et al, 2009;Clarke et al, 2016;Liang et al, 2016;Snyder, Kaiser, Warren, & Heller, 2015;Weiner et al, 2015) have been reported in all the disorders being studied in this project. We use tasks that were previously developed at NIMHANS for tb-fMRI acquistions: Tool for Recognition of Emotions in Neuropsychiatric Disorders (TRENDS) (Behere et al, 2008), which is a standardized validated tool for studying emotion recognition deficits in Indian patients, and Verbal Fluency Task (VFT) , which is a semantic category overt word generation task that is implemented as a blocked design.…”
Section: Task-based Fmrimentioning
confidence: 64%
“…Abnormalities in emotion recognition (Castellano et al, 2015;Daros, Zakzanis, & Rector, 2014;Elferink, van, & Kessels, 2015;Homorogan et al, 2017;Kohler, Walker, Martin, Healey, & Moberg, 2010) and verbal fluency (Cardenas, Kassem, Brotman, Leibenluft, & McMahon, 2016;Clark et al, 2009;Clarke et al, 2016;Liang et al, 2016;Snyder, Kaiser, Warren, & Heller, 2015;Weiner et al, 2015) have been reported in all the disorders being studied in this project. We use tasks that were previously developed at NIMHANS for tb-fMRI acquistions: Tool for Recognition of Emotions in Neuropsychiatric Disorders (TRENDS) (Behere et al, 2008), which is a standardized validated tool for studying emotion recognition deficits in Indian patients, and Verbal Fluency Task (VFT) , which is a semantic category overt word generation task that is implemented as a blocked design.…”
Section: Task-based Fmrimentioning
confidence: 64%
“…Abnormalities in emotion recognition (Castellano et al, 2015;Daros et al, 2014;Elferink et al, 2015;Homorogan et al, 2017;Kohler et al, 2010) and verbal fluency (Cardenas et al, 2016;Clark et al, 2009Clark et al, , 2016Liang et al, 2016;Snyder et al, 2015;Weiner et al, 2015) have been reported in all the disorders being studied in this project. We use tasks that were previously developed at NIMHANS for tb-fMRI acquisitions: TRENDS (Behere et al, 2008), which is a standardized validated tool for studying emotion recognition deficits in the Indian context, and VFT (John et al, 2011), which is a semantic category overt word generation task that is implemented as a blocked design.…”
Section: Task-based Fmrimentioning
confidence: 64%